2018
DOI: 10.4317/jced.54843
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three adhesive systems in class II composite restorations in endodontically treated teeth: Influence of Er:YAG laser conditioning and gingival margin levels on microleakage

Abstract: BackgroundDental surface conditioning by Er:YAG laser is currently being investigated, as not all of the mechanisms and effects of this technique have been clearly studied. Thus, the aim of the present study was to assess the cervical microleakage of Class II resin composite restorations in endodontically treated teeth following either the respective conventional conditioning or additional Er:YAG laser conditioning, in association with varied adhesives.Material and MethodsStandardized mesial-occlusal-distal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…[29][30][31][32][33] The lower bond strength can be attributed to the lack of resin penetration in laser-ablated dentin, showing the fusion of collagen fibrils, and the lack of interfibrillar space. 30 Consistent with our findings, Onay et al 34 found that neither the conditioning modality (Er:YAG laser) nor the adhesive systems affected the microleakage in class II composite restorations at enamel and dentin margins. Borsatto et al 35 assessed the effect of acid-etching and Er:YAG laser (120 mJ; 4 Hz) per se and in combination on the fissure sealant microleakage on primary teeth.…”
Section: Discussionsupporting
confidence: 91%
“…[29][30][31][32][33] The lower bond strength can be attributed to the lack of resin penetration in laser-ablated dentin, showing the fusion of collagen fibrils, and the lack of interfibrillar space. 30 Consistent with our findings, Onay et al 34 found that neither the conditioning modality (Er:YAG laser) nor the adhesive systems affected the microleakage in class II composite restorations at enamel and dentin margins. Borsatto et al 35 assessed the effect of acid-etching and Er:YAG laser (120 mJ; 4 Hz) per se and in combination on the fissure sealant microleakage on primary teeth.…”
Section: Discussionsupporting
confidence: 91%
“…Most studies identified by the reviewers focused on Er:YAG lasers, a type of laser with application in cavity preparations in dental practice. Studies compared laser conditioning with conventional 37% phosphoric acid, revealing that the two methods can provide similar shear bond strengths [ 28 , 31 , 32 , 35 , 36 ]. There are certain studies revealing even a higher bond strength for laser etching [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain satisfactory adhesion of glass fiber posts to the root dentin is a primordial requirement, the smear layer removal, as well as the complete removal of all the remaining of endodontic sealer and gutta-percha on the walls of the canal. 1 For this purpose, several chelating solutions are used, especially before the intracanal medication and the root canal filling. 2 The most widely used chelating agent is 17% EDTA, which acts on the inorganic portion of the dentin, exposing the dentin tubules.…”
Section: Discussionmentioning
confidence: 99%
“…The restoration of endodontically treated teeth has been generated discussions over the years. 1 This procedure becomes extremely complex when teeth involved feature a large loss of tooth structure and reduction of resistance. 2 Before a endodontically treated tooth restoration a clinical and radiographic assessment is important for appropriate planning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation